Answer: Option C.
Explanation:
A) The result of the substitution shown in Option A is obtained by solving for y from the first equation and substituting into the second equation:
![2x + y = 7\\y=7-2x](https://img.qammunity.org/2020/formulas/mathematics/high-school/j4hh8lw3uuwf9w0k2859o9u1ewpyss363y.png)
![y - x = 1\\7-2x-x=1](https://img.qammunity.org/2020/formulas/mathematics/high-school/e16dam1szl78smb9r5yiqy98l7rya8kcgq.png)
Therefore, this is a result of a substitution in the given system.
B) The result of the substitution shown in Option B is obtained by solving for y from the second equation and substituting into the first equation:
![y - x = 1](https://img.qammunity.org/2020/formulas/mathematics/high-school/3woixcmp8cde66fofte1oze7t5lq07b1do.png)
![y=x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rwcyp2zhoac783ugzjl02t5nu74wceg9ee.png)
![2x + y = 7\\2x + x + 1 = 7](https://img.qammunity.org/2020/formulas/mathematics/high-school/bhpmwc81p075y3gn4h2m5k9vn4vrr04a34.png)
Therefore, this is a result of a substitution in the given system.
C) The result of the substitution shown in Option C is not a result of a substitution in the given system, because if you solve for x from the second equation and substitute into the first one, you get:
![y-x=1\\(-1)(-x)=(-y+1)(-1)\\x=y-1\\\\2(y - 1) + y = 7](https://img.qammunity.org/2020/formulas/mathematics/high-school/8n86ydvi9lpa6jfyftx9edgejvyczb4ihy.png)